HUBUNGAN PERAN KADER KESEHATAN DAN GURU DENGAN IMPLEMENTASI IMUNISASI MR (MEASLES RUBELLA) DI WILAYAH KERJA PUSKESMAS TALAGA JAYA KABUPATEN GORONTALO - Dewi Modjo; Wiwi Susanti Piola; Eka Putri Latif (Zaitun (Jurnal Ilmu Kesehatan), 2020)
Measles Rubella immunization is combination of Measles and Rubella vaccine for protection against Measles and Rubella. The objective of research was to determine the relationship of nurse officer roles and teacher with the implementation of Measles Rubella immunization. The design used analytic quantitative survey with cross sectional approach. Sampling technique used Total sampling with 42 samples of nurse officer and teacher. Analysis used chi square with the significant   = 0,05, the result obtained there is  relationship between nurse officer with the implementation of MR immunization with ρ = 0,026 < 0,05, and also there is  relationship between teacher with the implementation of MR immunization with ρ = 0,022 < 0,05.